A method for identifying support conditions of buried subsea gas pipelines based on forced vibration signal analysis. (February 2019) - Liao, Ningsheng; Zhang, Hang; Zhang, Shimin; Du, Shuqiang; Ding, Qingxin
Subsea pipeline is crucial for oil and gas transportation. It is advantageous to be able to identify the free-spanning segments of a long subsea pipeline. The existing technologies for detecting the support condition of buried subsea pipelines are constantly affected by complex external environment since they are outer pipeline detecting methods. An inner pipeline method for detecting the support conditions of buried gas subsea pipelines based on forced vibration signal analysis is proposed in this study. Two evaluation indicators, frequency response function and natural frequency change ratio, are used to identify the free-spanning segments. A free span–detecting device and a test rig are built to verify the applicability of the method by forced vibration tests. Gray contour plots of frequency response functions and natural frequency change ratio bar charts are generated to analyze the experimental results. The experimental results show that two evaluation indicators are sensitive to the support condition. The appearance of the free span and its length can be identified by the gray contour plots of frequency response functions and natural frequency change ratio bar chart.